2021
DOI: 10.1111/1365-2745.13584
|View full text |Cite
|
Sign up to set email alerts
|

Fungal root endophytes influence plants in a species‐specific manner that depends on plant's growth stage

Abstract: The mycobiome (fungal microbiome) influences plants—from seed germination to full maturation. While many studies on fungal‐plant interaction studies have focused on known mutualistic and pathogenic fungi, the functional role of ubiquitous endophytic fungi remains little explored. We examined how root‐inhabiting fungi (endophytes) influence range‐expanding plant species. We isolated endophytes from three European intra‐continental range‐expanders and three congenerics that are native both in the range expander'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 87 publications
2
16
0
Order By: Relevance
“…However, not all fungal inoculations participated in plant growth promotion. Regardless of the single or combined inoculations, the effects mainly depended on different fungal species and combinations, which approved the previous reports that fungal species may be one of the factors influencing symbiotic relationships and plant performance (Wazny et al, 2018 ; Geisen et al, 2021 ). Liu et al ( 2020b ) found that the synergistic effect of arbuscular mycorrhizal fungi and endophytic fungi on tall fescue depended on the species of arbuscular mycorrhizal fungi.…”
Section: Discussionsupporting
confidence: 84%
“…However, not all fungal inoculations participated in plant growth promotion. Regardless of the single or combined inoculations, the effects mainly depended on different fungal species and combinations, which approved the previous reports that fungal species may be one of the factors influencing symbiotic relationships and plant performance (Wazny et al, 2018 ; Geisen et al, 2021 ). Liu et al ( 2020b ) found that the synergistic effect of arbuscular mycorrhizal fungi and endophytic fungi on tall fescue depended on the species of arbuscular mycorrhizal fungi.…”
Section: Discussionsupporting
confidence: 84%
“…The plant growth stage could change the impact of plant host-associated microbes, and such an impact is always strongest in early plant growth stages (Bagchi et al, 2014; Jevon et al, 2020). One potential reason is that small seedlings usually allocate most of their resources to survive and grow, while older seedlings have relatively more resources to defend against pathogen infection (Geisen et al, 2021; Schloter & Matyssek, 2009). For example, smaller seedlings were more sensitive to inoculated individual fungi, soil microbiota or litter addition than older seedlings due to fewer defense resources and little chance of recovering from biomass loss (Geisen et al, 2021; Jevon et al, 2020; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One potential reason is that small seedlings usually allocate most of their resources to survive and grow, while older seedlings have relatively more resources to defend against pathogen infection (Geisen et al, 2021; Schloter & Matyssek, 2009). For example, smaller seedlings were more sensitive to inoculated individual fungi, soil microbiota or litter addition than older seedlings due to fewer defense resources and little chance of recovering from biomass loss (Geisen et al, 2021; Jevon et al, 2020; Zhang et al, 2022). Another possible reason is related to the interaction between seed-borne microbes and peripheral microbial sources in young seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these hits were in other strains of Pyricularia oryzae (M. oryzae teleomorph), which is not strange. Maybe more interesting, common to all hits, including the ones in M.oryzae , they are all fungi known to produce melanized hydrophobic structures (Collado et al ., 2002; Liu et al ., 2009; Kokaew et al ., 2011; Al-Khawaldeh et al ., 2020; Geisen et al ., 2021; Sarsaiya et al ., 2020; Li et al ., 2016; Gao et al ., 2021; Chen et al ., 2021) indicating that our results showing a possible involvement of MoMyb13 in hydrophobin production could be relevant also for these similar proteins in diverse fungi all belonging to the class Sordariomycetes. Interestingly, all these melanized fungi are also known to grow endophytically, as M. oryzae do in the first biotrophic stages of infection (Kankanala et al ., 2007) when MoMyb13 is upregulated ( Fig.…”
Section: Discussionmentioning
confidence: 99%